2016
DOI: 10.3892/ijo.2016.3351
|View full text |Cite
|
Sign up to set email alerts
|

Genistein-induced differentiation of breast cancer stem/progenitor cells through a paracrine mechanism

Abstract: Abstract. It is believed that breast cancer stem cells (BCSCs), like normal stem cell counterparts, have the capacity of selfrenewal and differentiation. Simultaneously, estrogen receptor (ER)-negative (-) BCSCs are affected by surrounding differentiated ER-positive (+) tumor cells by virtue of paracrine signaling within the tumor micro environment. Genistein (GEN), as a sort of phytoestrogen, can act on ER + breast cancer cells but the role of GEN in the differentiation of neighboring ER -BCSCs has not been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Genistein inhibits tumorsphere formation, suppresses cell invasive capacity, and reduces chemoresistance in gastric cancer cells (Huang et al, ; Yu et al, ). Genistein decreases the population and induces differentiation of breast CSCs (Fan et al, ; Liu et al, ). However, the action of genistein on NCSCs has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein inhibits tumorsphere formation, suppresses cell invasive capacity, and reduces chemoresistance in gastric cancer cells (Huang et al, ; Yu et al, ). Genistein decreases the population and induces differentiation of breast CSCs (Fan et al, ; Liu et al, ). However, the action of genistein on NCSCs has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…BC is one of the most common malignancies in women, and its incidence rate is the second highest in the world (18)(19)(20). Despite the existence of tumor stem cells in a variety of solid tumors and hematologic malignancies, there are presently many problems to be solved (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that genistein abolishes stemness in CSCs or CSLCs via inhibition of AKT phosphorylation and activity (10,16). We thus hypothesized that the novel genistein analogue DFOG-inhibited spheroid and colony formation is associated with AKT inactivation.…”
Section: Dfog Reduces the Phosphorylation Levels Of Akt Inmentioning
confidence: 94%